Gainsborough - Kalinsky, Nicola (Phaidon colour library, 1995)
This work analyzes Gainsborough's techniques and subject matter, and explores his artistic environment, his important contemporaries and issues such as the patronage of artists in 18th-century England. It also contains a survey of Gainsborough's most famous works, including 'The Blue Boy'.